All-solid-state battery and application thereof

By combining the three-layer solid electrolyte membrane structure, the compatibility and stability of the solid electrolyte membrane of all-solid state batteries are improved, and the problem of insufficient characteristics of the solid electrolyte membrane in the battery is solved, which extends the cycle life of the battery and enhances safety and working efficiency. .

CN119253025APending Publication Date: 2025-01-03ENVISION AESC JAPAN LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411545111.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The solid electrolyte membrane of all-solid state batteries cannot meet the characteristics of high ion conductivity, lithium dendrite penetration resistance, high voltage and reduction resistance, which limits the development and application of batteries.

Method used

The composite three-layer solid electrolyte membrane structure is adopted, wherein the ionic conductivity of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer are 1×10-4S/cm to 1×10-2S/cm, respectively, through Specific chemical composition and preparation process to improve membrane compatibility and stability.

Benefits of technology

It improves the compatibility between the solid electrolyte membrane and the positive and negative electrodes, extends the cycle life of the battery, enhances the safety and working efficiency of the battery, and avoids the short circuit problem caused by lithium dendrites penetration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253025A_ABST
    Figure CN119253025A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state battery and application thereof, the all-solid-state battery at least comprises: a first solid electrolyte layer arranged on the positive electrode side of the all-solid-state battery, the ionic conductivity of the first solid electrolyte layer being 1 * 10 <-4 > S / cm to 1 * 10 <-2 > S / cm; a second solid-state electrolyte layer provided on the negative electrode side of the all-solid-state battery, the ionic conductivity of the second solid-state electrolyte layer being 1 * 10 <-3 > S / cm to 2 * 10 <-2 > S / cm; and a third solid-state electrolyte layer provided between the first solid-state electrolyte layer and the second solid-state electrolyte layer, the third solid-state electrolyte layer having an ionic conductivity of 1 * 10 <-3 > S / cm to 2 * 10 <-2 > S / cm. According to the all-solid-state battery and the application thereof provided by the invention, the lithium dendrite penetration resistance of the solid electrolyte membrane in the all-solid-state battery can be improved, and the ionic conductivity, the electrochemical reduction stability and the compatibility between a positive electrode and a negative electrode of the solid electrolyte membrane are improved, so that the cycle life of the battery is prolonged, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to an all-solid-state battery and applications thereof. Background Art

[0002] With the rapid development of industries such as new energy vehicles and wearable devices, the demand for lithium-ion batteries with high energy density, long cycle life and high safety is growing. Among them, all-solid-state batteries have attracted widespread attention due to their advantages such as excellent ion conductivity, mechanical strength and thermal stability. However, in the actual application of all-solid-state batteries, solid electrolyte membranes cannot simultaneously meet the characteristics of high ion conductivity, resistance to lithium dendrite penetration, high voltage resistance and reduction resistance, which seriously restricts the development and application of all-solid-state batteries. Summary of the invention

[0003] The present invention proposes an all-solid-state battery and its application. Through the all-solid-state battery and its application provided by the present invention, the resistance of the solid electrolyte membrane in the all-solid-state battery to lithium dendrite penetration can be improved, the ionic conductivity, electrochemical reduction stability of the solid electrolyte membrane, and the compatibility with the positive and negative electrodes can be improved, thereby improving the cycle life and safety of the battery.

[0004] In order to solve the above technical problems, the present invention provides an all-solid-state battery, comprising at least:

[0005] The first solid electrolyte layer is arranged on the positive electrode side of the all-solid-state battery, and the ion conductivity of the first solid electrolyte layer is 1×10 -4 S / cm~1×10 -2 S / cm;

[0006] The second solid electrolyte layer is arranged on the negative electrode side of the all-solid-state battery, and the ion conductivity of the second solid electrolyte layer is 1×10 -3 S / cm~2×10 -2 S / cm; and

[0007] The third solid electrolyte layer is disposed between the first solid electrolyte layer and the second solid electrolyte layer, and the ionic conductivity of the third solid electrolyte layer is 1×10 -3 S / cm~2×10 -2 S / cm.

[0008] In one embodiment of the present invention, the first solid electrolyte layer includes a first electrolyte, and the chemical formula of the first electrolyte is Li 2+n Zr 1-n M n Cl 6-x-y Br x I y, where \(0\leq n\leq0.6\), \(0\leq x\leq6\), \(0\leq y\leq6\), \(x + y\leq6\), and \(M\) is selected from at least one of \(V\), \(Cr\), \(Mn\), \(Fe\), \(Co\), or \(Ni\).

[0009] In one embodiment of the present invention, \(M\) is \(Fe\), and the value range of \(n\) is \(0.01\leq n\leq0.5\).

[0010] In one embodiment of the present invention, the second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is \(Li\) a P 1-b T b S c O d X e , where \(5 < a < 6\), \(0 < b < 1\), \(1.5 < c < 5\), \(0 < d < 2.5\), \(4 < c + d < 5\), \(1 < e < 2\), \(T\) is selected from at least one of \(Al\), \(Ga\), \(In\), \(Ti\), \(Sc\), \(As\), \(Sb\), \(Bi\), \(As\), \(V\), or \(Nb\), and \(X\) is selected from at least one of \(Cl\), \(Br\), or \(I\).

[0011] In one embodiment of the present invention, \(T\) is selected from at least one of \(Sb\), \(In\), or \(Bi\), \(X\) is \(Cl\), and the value range of \(b\) is \(0 < b\leq0.1\).

[0012] In one embodiment of the present invention, the second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is \(Li\) f P 1-g E g S w O g Q z , where \(5 < f < 10\), \(0 < g < 1\), \(3 < w < 6\), \(4 < w + g < 6\), \(0 < z < 2\), \(E\) is selected from at least one of \(Mg\), \(Ca\), \(Sr\), \(Ba\), \(Zn\), \(Cr\), \(Sn\), or \(Pb\), and \(Q\) is selected from at least one of \(Cl\), \(Br\), or \(I\).

[0013] In one embodiment of the present invention, \(E\) is \(Mg\), \(Q\) is \(Cl\), and the value range of \(g\) is \(0.01\leq g\leq0.1\).

[0014] In one embodiment of the present invention, the third solid electrolyte layer includes the second electrolyte and a third electrolyte, and the chemical formula of the third electrolyte is \(Li\) 10 Ge 1-i G i P 2 S 12 , where \(0\leq i < 1\), and \(G\) is selected from at least one of \(Si\) or \(Sn\).

[0015] In one embodiment of the present invention, in the third solid electrolyte layer, the content of the second electrolyte is 1wt%-95wt%, and the content of the third electrolyte is 5wt%-99wt%.

[0016] In one embodiment of the present invention, the thickness of the first solid electrolyte layer is 1 μm-100 μm, the thickness of the second solid electrolyte layer is 1 μm-150 μm, and the thickness of the third solid electrolyte layer is 1 μm-100 μm.

[0017] The present invention also provides an electronic device, comprising the above-mentioned all-solid-state battery.

[0018] In summary, the present invention proposes an all-solid-state battery and its application. By improving the solid electrolyte membrane in the all-solid-state battery, the compatibility between the solid electrolyte membrane and the positive and negative electrodes can be improved, and the electrochemical window of the solid electrolyte membrane can be widened, thereby improving the stability of the all-solid-state battery. The resistance of the solid electrolyte membrane to lithium dendrite penetration can be improved, the battery can be prevented from short-circuiting, and the all-solid-state battery can still operate stably and safely at high rates, thereby improving the safety and cycle life of the battery. The ionic conductivity of the solid electrolyte membrane can be improved, thereby improving the working efficiency of the battery. The electrochemical reduction stability of the solid electrolyte membrane can be improved, so that the solid electrolyte membrane can effectively resist the reduction reaction and the instability of the electrode interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0020] Figure 1 Schematic diagram of the structure of an all-solid-state battery in one embodiment of the present invention.

[0021] Figure 2 Schematic diagram of the process of preparing the first solid electrolyte layer and the second solid electrolyte layer in one embodiment of the present invention.

[0022] Figure 3 FIG. 5 is a scanning electron microscope image of a solid electrolyte membrane in one embodiment of the present invention.

[0023] Figure 4 This is a graph showing the results of a room temperature cycle performance test on the all-solid-state battery in Example 3 of the present invention.

[0024] Marking Description:

[0025] 10. All-solid-state battery; 11. Positive electrode; 12. Negative electrode; 13. Solid electrolyte membrane; 131. First solid electrolyte layer; 132. Second solid electrolyte layer; 133. Third solid electrolyte layer. DETAILED DESCRIPTION

[0026] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0027] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0028] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] See also Figure 1 As shown, the present invention proposes an all-solid-state battery 10, for example, including a positive electrode 11, a negative electrode 12 and a solid electrolyte membrane 13, wherein the solid electrolyte membrane 13 is arranged between the positive electrode 11 and the negative electrode 12, and the solid electrolyte membrane 13, for example, includes a first solid electrolyte layer 131, a second solid electrolyte layer 132 and a third solid electrolyte layer 133, the first solid electrolyte layer 131 is arranged on the positive electrode 11 side, the second solid electrolyte layer 132 is arranged on the negative electrode 12 side, and the third solid electrolyte layer 133 is arranged between the first solid electrolyte layer 131 and the second solid electrolyte layer 132. In the all-solid-state battery 10 provided by the present invention, the resistance to lithium dendrite penetration, electrochemical reduction stability, and compatibility between the solid electrolyte membrane 13 and the positive and negative electrodes can be improved. In the present invention, the all-solid-state battery 10 is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type and type of the all-solid-state battery 10.

[0030] See also Figure 1As shown, in one embodiment of the present invention, the positive electrode 11 includes, for example, a positive electrode active material, a solid electrolyte, a conductive agent, and a binder. Among them, the positive electrode active material is, for example, selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA), and the solid electrolyte is, for example, a halide electrolyte that does not react with the positive electrode active material to generate heat, so as to improve the safety of the battery. The conductive agent is, for example, selected from at least one of conductive carbon black (SuperP), nanocarbon fiber (Vapor-grown carbon fiber, VGCF), acetylene black, carbon nanotubes or graphene. The binder is, for example, selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride, polyethylene oxide, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, ethylene-propylene-diene terpolymer, polyhexafluoropropylene or styrene-butadiene rubber. The present invention does not limit the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder, and the ratio can be selected according to actual needs.

[0031] See also Figure 1 As shown, in one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O 2 , the chemical formula of the halide electrolyte is, for example, Li 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5 The conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP and VGCF is, for example, 1:1, and the binder is, for example, PTFE. The positive electrode active material, the halide solid electrolyte, the conductive agent and the binder are mixed evenly in a mass ratio of, for example, 69:29:1:1, and the positive electrode 11 is obtained by dry pressing.

[0032] See also Figure 1 As shown, in one embodiment of the present invention, the negative electrode 12 is, for example, metallic lithium.

[0033] See also Figure 1 As shown, in one embodiment of the present invention, the thickness of the solid electrolyte membrane 13 is, for example, 5 μm to 200 μm, and the ionic conductivity is, for example, 1×10 -4 S / cm~2×10 -2Specifically, in the solid electrolyte membrane 13, the thickness of the first solid electrolyte layer 131 is, for example, 1 μm to 100 μm, and the ion conductivity is, for example, 1×10 -4 S / cm~1×10 -2 S / cm, the thickness of the second solid electrolyte layer 132 is, for example, 1 μm to 150 μm, and the ionic conductivity is, for example, 1×10 -3 S / cm~2×10 -2 S / cm, the thickness of the third solid electrolyte layer 133 is, for example, 1 μm to 100 μm, and the ionic conductivity is, for example, 1×10 -3 S / cm~2×10 -2 S / cm. By using a composite three-layer solid electrolyte layer as the solid electrolyte membrane 13, the ionic conductivity of the solid electrolyte membrane 13 can be improved, thereby improving the working efficiency of the all-solid-state battery 10. Moreover, by controlling the thickness of the solid electrolyte membrane 13, the first solid electrolyte layer 131 and the second solid electrolyte layer 132, the cycle performance of the all-solid-state battery 10 can be improved, thereby extending the service life of the battery.

[0034] See also Figure 1 As shown, in one embodiment of the present invention, the first solid electrolyte layer 131 includes a first electrolyte, which is, for example, a high-voltage resistant halide electrolyte, which can widen the electrochemical window of the solid electrolyte membrane 13, so that the solid electrolyte membrane 13 can adapt to the high-voltage positive electrode, and improve the compatibility between the solid electrolyte membrane 13 and the positive electrode 11. Specifically, the chemical formula of the first electrolyte is, for example, Li 2+n Zr 1-n M n Cl 6-x-y Br x I y , wherein 0≤n≤0.6, 0≤x≤6, 0≤y≤6, x+y≤6, and M is selected from at least one of V, Cr, Mn, Fe, Co, or Ni. Further, M is, for example, Fe, and the value range of n is 0.01≤n≤0.5, and specifically, n is, for example, 0.35. By controlling the type of the M element in the first electrolyte and the value range of n, the chemical stability and lithium ion conductivity of the first solid electrolyte layer 131 can be improved.

[0035] See also Figure 1 to Figure 2 As shown, in one embodiment of the present invention, when preparing the first solid electrolyte layer 131, firstly, in an atmosphere of an inert gas such as argon, according to the chemical formula of the first electrolyte Li 2+n Zr 1-n M n Cl 6-x-y Br x I y, after the Li source, Zr source, M source, Cl source, Br source and I source are uniformly mixed according to the stoichiometric ratio, for example, placed in a ball mill for ball milling to obtain a first electrolyte. The Li source is, for example, selected from at least one of LiCl, LiBr or LiI, and the Zr source is, for example, ZrCl 4 , the M source is, for example, chloride of M, the Cl source is, for example, at least one of a Li source, a Zr source or an M source, the Br source and the I source are, for example, from a Li source, the ball material mass ratio is, for example, (1-100):1, the ball milling time is, for example, 1h-72h, and the rotation speed is, for example, 100rpm-1500rpm. After obtaining the first electrolyte, the first solid electrolyte layer 131 is prepared by, for example, a powder extrusion molding method, a wet coating method, or an electrostatic spraying method.

[0036] See also Figure 2 As shown, in one embodiment of the present invention, when the first solid electrolyte layer 131 is prepared by powder extrusion molding, the first electrolyte and the first binder are firstly mixed evenly, for example, by low-temperature shear mixing, and then the mixture is rapidly heated up for high-temperature shear mixing to obtain a mixture, and then the mixture is added to a roller press for high-temperature rolling to obtain the first solid electrolyte layer 131. Among them, the first binder is, for example, selected from at least one of PTFE, ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-trifluorochloroethylene copolymer, the content of the first electrolyte in the mixed material is, for example, 95wt% to 99.9wt%, the content of the first binder in the mixed material is, for example, 0.1wt% to 5wt%, the temperature of low-temperature shearing is, for example, -30℃ to 15℃, the temperature of high-temperature shearing is, for example, 20℃ to 200℃, and the temperature of high-temperature rolling is, for example, 20℃ to 200℃.

[0037] See also Figure 1As shown, in another embodiment of the present invention, when the first solid electrolyte layer 131 is prepared by wet coating or electrostatic spraying, the first electrolyte, the second binder and the solvent are firstly mixed evenly to obtain a mixed component, and then the mixed component is coated on the substrate by wet coating or electrostatic spraying, and then the substrate coated with the mixed component is dried at high temperature and peeled off to obtain the first solid electrolyte layer 131. The second binder is, for example, selected from PVDF, carboxymethyl cellulose ((Carboxymethyl Cellulose, CMC), styrene butadiene rubber (Polymerized Styrene Butadiene Rubber, SBR), polyvinyl pyrrolidone (Polyvinyl pyrrolidone, PVP), polymethyl methacrylate (Polymethyl Methacrylate, PMMA), polyacrylonitrile (Polyacrylonitrile, PAN), polyacrylic acid (Polyacrylic acid, PAA), polyurethane, polyvinyl alcohol (Polyvinyl alcohol, PVA), sodium alginate (Sodium alginate, Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, polyvinylidene fluoride, fluororubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer, etc., the solvent is selected from toluene, chlorobenzene, xylene, dimethyl carbonate, N- At least one of methylformamide, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone, etc., the content of the first electrolyte in the mixed component is 30wt% to 90wt%, the content of the second binder in the mixed component is, for example, 0.1wt% to 10wt%, the content of the solvent in the mixed component is, for example, 10wt% to 50wt%, the substrate is, for example, selected from polyethylene glycol terephthalate (PET) film, smooth aluminum foil or release paper, and the temperature of high-temperature drying is, for example, 30°C to 250°C.

[0038] See also Figure 1 As shown, in one embodiment of the present invention, the second solid electrolyte layer 132 includes a second electrolyte, and the second electrolyte is, for example, a reduction-resistant sulfide electrolyte, which can improve the electrochemical reduction stability of the solid electrolyte membrane 13. Specifically, the chemical formula of the second electrolyte is, for example, selected from Li a P1-b T b S c O d X e or Li f P 1-g E g S w O g Q z at least one of the following. Among them, in Li a P 1-b T b S c O d X e where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, T is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, or Nb, etc., and X is selected from at least one of Cl, Br, or I, etc. Further, T is, for example, selected from at least one of Sb, In, or Bi, X is Cl, the value range of b is, for example, 0 < b ≤ 0.1. More specifically, when T is, for example, a +5 valence element, b is, for example, 0.04, and when T is, for example, a +3 valence element, b is, for example, 0.02. By controlling the types of elements T and X in the second electrolyte and the value range of b, the cycle performance of the all-solid-state battery 10 can be improved, thereby extending the service life of the battery.

[0039] Please refer to Figure 1 as shown. In an embodiment of the present invention, when the chemical formula of the second electrolyte is Li f P 1-g E g S w O g Q z where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, or Pb, etc., and Q is selected from at least one of Cl, Br, or I, etc. Further, E is, for example, Mg, Q is, for example, Cl, the value range of g is, for example, 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the type of element E, the type of element Q, and the value range of g in the second electrolyte, the cycle performance of the all-solid-state battery 10 can be improved, thereby extending the service life of the battery.

[0040] Please refer to Figure 1 as shown. In an embodiment of the present invention, when preparing the first solid electrolyte layer 131, first, in an atmosphere of an inert gas such as argon, according to the chemical formula of the second electrolyte Li a P 1-b T bS c O d X e or Li f P 1-g E g S w O g Q z , Li source, P source, T source, S source and X source, or Li source, P source, E source, S source and Q source are mixed evenly according to stoichiometric ratio, for example, placed in a ball mill for ball milling to obtain a precursor powder, and then the precursor powder is annealed and sintered at high temperature to obtain a second electrolyte. Wherein, the Li source is, for example, selected from Li 2 At least one of S, LiCl, LiBr or LiI, etc., the P source is, for example, P 2 S 5 , T source is, for example, an oxide of T, S source is, for example, at least one of a Li source or a P source, X source is, for example, a Li source, E source is, for example, an oxide of E, Q source is, for example, a Li source, the ball material mass ratio is, for example, (1-100):1, the ball milling time is, for example, 1h-48h, the rotation speed is, for example, 50rpm-1500rpm, the sintering temperature is, for example, 400℃-600℃, and the sintering time is, for example, 1h-48h. After obtaining the second electrolyte, the second solid electrolyte layer 132 is prepared, for example, by powder extrusion molding, wet coating, or electrostatic spraying. The process of preparing the second solid electrolyte layer 132 by powder extrusion molding, wet coating, or electrostatic spraying is the same as the process of preparing the first solid electrolyte layer 131 by powder extrusion molding, wet coating, or electrostatic spraying, and will not be elaborated here.

[0041] See also Figure 1 As shown, in one embodiment of the present invention, the third solid electrolyte layer 133 includes a second electrolyte and a third electrolyte. The second electrolyte is the same as the second electrolyte in the second solid electrolyte layer 132, and will not be elaborated here. The third electrolyte is, for example, a lithium reduction reaction type sulfide electrolyte, which can consume the generated lithium dendrites, prevent the penetration of lithium dendrites, avoid short circuit of the all-solid-state battery 10, and ensure that the all-solid-state battery 10 can still operate stably and safely at a high rate. Specifically, in the third solid electrolyte layer 133, the content of the second electrolyte is, for example, 1wt%-95wt%, and the content of the third electrolyte is, for example, 5wt%-99wt%. Among them, the chemical formula of the third electrolyte is, for example, Li 10 Ge 1-i G i P 2 S 12, wherein 0≤i<1, and G is selected from at least one of Si or Sn. Specifically, in this embodiment, i is, for example, 0. By controlling the value of i, the cycle performance of the all-solid-state battery 10 can be improved, thereby extending the service life of the battery.

[0042] See also Figure 1 to Figure 2 As shown, in one embodiment of the present invention, when preparing the third solid electrolyte layer 133, first, in an atmosphere of an inert gas such as argon, according to the chemical formula of the third electrolyte Li 10 Ge 1-i G i P 2 S 12 , after the Li source, Ge source, G source, P source and S source are mixed evenly according to the stoichiometric ratio, for example, placed in a ball mill for ball milling to obtain a third electrolyte precursor powder, and then the second electrolyte precursor powder is subjected to high temperature annealing and sintering to obtain a third electrolyte. Among them, the Li source is, for example, Li 2 S, Ge source, for example, GeS 2 The G source is, for example, a sulfide of G, and the P source is, for example, P 2 S 5 , the S source is, for example, from at least one of a Li source, a Ge source, a G source or a P source, the ball-to-material mass ratio is, for example, (1-100):1, the ball milling time is, for example, 1h-48h, the rotation speed is, for example, 50rpm-1000rpm, the sintering temperature is, for example, 500℃-800℃, and the sintering time is, for example, 1h-48h. Next, a second electrolyte is prepared according to the chemical formula of the second electrolyte. The preparation process of the second electrolyte is the same as the preparation process of the second electrolyte in the second solid electrolyte layer 132, and will not be elaborated here. After obtaining the second electrolyte and the third electrolyte, the second electrolyte and the third electrolyte are mixed evenly to obtain a mixed electrolyte material, and then the third solid electrolyte layer 133 is prepared by, for example, a powder extrusion molding method, a wet coating method or an electrostatic spraying method. Among them, the process of preparing the third solid electrolyte layer 133 by powder extrusion molding method, wet coating method or electrostatic spraying method is the same as the process of preparing the first solid electrolyte layer 131 by powder extrusion molding method, wet coating method or electrostatic spraying method, and will not be elaborated here.

[0043] See also Figure 1As shown, in one embodiment of the present invention, when preparing the solid electrolyte membrane 13, the first solid electrolyte layer 131, the third solid electrolyte layer 133 and the second solid electrolyte layer 132 are rolled in sequence to form a solid electrolyte membrane 13. Among them, the first solid electrolyte layer 131 can widen the electrochemical window of the solid electrolyte membrane 13, so that the solid electrolyte membrane 13 can adapt to the high-voltage positive electrode 11 and the lithium metal negative electrode 12, the second solid electrolyte layer 132 can improve the electrochemical reduction stability of the solid electrolyte membrane 13, and improve the interface stability between the solid electrolyte membrane 13 and the negative electrode 12 to ensure a continuous and stable lithium ion transmission channel, and the third solid electrolyte layer 133 can consume the generated lithium dendrites, prevent the lithium dendrites from penetrating, avoid the short circuit of the all-solid-state battery 10, and ensure that the all-solid-state battery 10 can still operate stably and safely at a high rate.

[0044] See also Figure 1 As shown, in one embodiment of the present invention, the above-mentioned positive electrode 11, solid electrolyte membrane 13 and negative electrode 12 are sequentially stacked, packaged, hot pressed and cold pressed to assemble into an all-solid-state battery 10.

[0045] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0046] Example 1

[0047] Preparation of the first electrolyte: 1.35 mol of LiCl, 0.5 mol of LiBr, 0.5 mol of LiI, and 0.65 mol of ZrCl 4 and 0.35 mol FeCl 3 High energy ball milling was performed to obtain Li 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5 Electrolyte materials.

[0048] Preparation of the second electrolyte: Under argon atmosphere, 2 mol of Li 2 S, 1.5 mol LiCl, 0.48 mol P 2 S 5 and 0.02 mol of Sb 2 O 5 High energy ball milling was performed to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl1.5 The precursor powder was sintered at 500 °C for 10 h and then cooled to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Electrolyte materials.

[0049] Preparation of the third electrolyte: Under argon atmosphere, 5 mol of Li 2 S, 1 mol of P 2 S 5 and 1 mol of GeS 2 High energy ball milling was performed to obtain Li 10 G 2 S 12 The precursor powder was sintered at 600 °C for 10 h and then cooled to obtain Li 10 G 2 S 12 Electrolyte materials.

[0050] Preparation of the first solid electrolyte layer: Li 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5 The electrolyte material and PTFE were mixed at a mass ratio of 99:1 at -20°C, and the temperature was raised to 80°C to fiberize the PTFE to obtain Li 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5 &PTFE mixed material. Then Li 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5 The PTFE mixed material was extruded into a roller press, and the electrolyte membrane was rolled to a thickness of 5 μm at 80°C by adjusting the roller press gap to form the first solid electrolyte layer.

[0051] Preparation of the second solid electrolyte layer: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5The electrolyte material and PTFE were mixed at a mass ratio of 99:1 at -20°C, and the temperature was raised to 80°C to fiberize the PTFE to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 &PTFE mixed material. Then Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The PTFE mixed material is extruded into a roller press, and the electrolyte membrane is rolled to a thickness of 20 μm at 80°C by adjusting the roller press gap to form a second solid electrolyte layer.

[0052] Preparation of the third solid electrolyte layer: 5wt% Li 10 G 2 S 12 Electrolyte materials and 95 wt% Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The electrolyte materials are mixed evenly to obtain a mixed electrolyte material. Then, the mixed electrolyte material and PTFE are mixed evenly at a mass ratio of 99:1 at -20°C, and the temperature is raised to 80°C to fiberize the PTFE to obtain a mixed material for preparing the third solid electrolyte layer. The mixed material is then extruded into a roller press, and the electrolyte membrane is rolled to a thickness of 5 μm at 80°C by adjusting the roller press gap to prepare the third solid electrolyte layer.

[0053] Preparation of solid electrolyte membrane: The first solid electrolyte layer, the third solid electrolyte layer and the second solid electrolyte layer are rolled and compounded in a roller press in sequence to form a solid electrolyte membrane.

[0054] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O 2 Positive electrode active material, Li 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5The halide solid electrolyte, the conductive agent and PTFE are mixed evenly in a mass ratio of 69:29:1:1, for example, and then the positive electrode is obtained by dry pressing. The conductive agent includes SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1.

[0055] Choice of negative electrode: Choose metallic lithium as the negative electrode.

[0056] Battery preparation: The positive electrode, solid electrolyte membrane and negative electrode are stacked, packaged, hot pressed and cold pressed in sequence to assemble into an all-solid-state soft-pack battery.

[0057] Example 2

[0058] The difference between this embodiment and embodiment 1 is that in the third solid electrolyte layer, the content of the second electrolyte is 50 wt %, and the content of the third electrolyte is 50 wt %.

[0059] Example 3

[0060] The difference between this embodiment and embodiment 1 is that in the third solid electrolyte layer, the content of the second electrolyte is 20 wt %, and the content of the third electrolyte is 80 wt %.

[0061] Example 4

[0062] The difference between this embodiment and embodiment 1 is that in the third solid electrolyte layer, the content of the second electrolyte is 1 wt %, and the content of the third electrolyte is 99 wt %.

[0063] Example 5

[0064] The difference between this embodiment and embodiment 3 is that the chemical formula of the third electrolyte is Li 10 Ge 0.5 Sn 0.5 P 2 S 12 The raw material is 1 mol of Li 2 S, 1 mol of P 2 S 5 , 0.5 mol GeS 2 and 0.5 mol SnS 2 .

[0065] Example 6

[0066] The difference between this embodiment and embodiment 3 is that the chemical formula of the third electrolyte is Li 10 Ge 0.5 Si 0.5 P 2 S 12 The raw material is 1 mol of Li 2S, 1 mol of P 2 S 5 , 0.5 mol GeS 2 and 0.5 mol SiS 2 .

[0067] Example 7

[0068] The difference between this embodiment and embodiment 3 is that the thickness of the first solid electrolyte layer is adjusted to 1 μm by adjusting the roller gap of the roller press.

[0069] Example 8

[0070] The difference between this embodiment and embodiment 3 is that the thickness of the first solid electrolyte layer is adjusted to 50 μm by adjusting the roller gap of the roller press.

[0071] Example 9

[0072] The difference between this embodiment and embodiment 3 is that the thickness of the first solid electrolyte layer is adjusted to 100 μm by adjusting the roller gap of the roller press.

[0073] Example 10

[0074] The difference between this embodiment and embodiment 3 is that the thickness of the third solid electrolyte layer is adjusted to 1 μm by adjusting the roller gap of the roller press.

[0075] Embodiment 11

[0076] The difference between this embodiment and embodiment 3 is that the thickness of the third solid electrolyte layer is adjusted to 50 μm by adjusting the roller gap of the roller press.

[0077] Example 12

[0078] The difference between this embodiment and embodiment 3 is that the thickness of the third solid electrolyte layer is adjusted to 100 μm by adjusting the roller gap of the roller press.

[0079] Example 13

[0080] The difference between this embodiment and embodiment 3 is that the thickness of the second solid electrolyte layer is adjusted to 1 μm by adjusting the roller gap of the roller press.

[0081] Embodiment 14

[0082] The difference between this embodiment and embodiment 3 is that the thickness of the second solid electrolyte layer is adjusted to 50 μm by adjusting the roller gap of the roller press.

[0083] Embodiment 15

[0084] The difference between this embodiment and embodiment 3 is that the thickness of the second solid electrolyte layer is adjusted to 150 μm by adjusting the roller gap of the roller press.

[0085] Example 16

[0086] The difference between this embodiment and embodiment 3 is that the chemical formula of the first electrolyte is Li 2.2 Zr 0.8 Fe 0.2 Cl 5 Br 0.5 I 0.5 The raw materials are 1.2 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, and 0.8 mol ZrCl 4 and 0.2 mol FeCl 3 .

[0087] Embodiment 17

[0088] The difference between this embodiment and embodiment 3 is that the chemical formula of the first electrolyte is Li 2.6 Zr 0.4 Fe 0.6 Cl 5 Br 0.5 I 0.5 The raw materials are 1.6 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, and 0.4 mol ZrCl 4 and 0.6 mol FeCl 3 .

[0089] Embodiment 18

[0090] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.5 P 0.99 Sb 0.01 S 4.47 5 O 0.025 Cl 1.5 The raw material is 2 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2 S 5 and 0.05 mol Sb 2 O 5 .

[0091] Embodiment 19

[0092] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.5 P 0.9 Sb 0.1 S4.25 O 0.25 Cl 1.5 The raw material is 2 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.05 mol Sb 2 O 5 .

[0093] Embodiment 20

[0094] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.5 P 0.96 Sb 0.04 S 4.4 0 O 0.10 Cl 1.3 Br 0.1 I 0.1 The raw material is 2 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.48 mol P 2 S 5 and 0.02 mol of Sb 2 O 5 .

[0095] Embodiment 21

[0096] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.52 P 0.99 Bi 0.01 S 4.48 5 O 0.015 Cl 1.5 The raw material is 2.01 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2 S 5 and 0.005 mol Bi 2 O 3 .

[0097] Embodiment 22

[0098] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.54 P 0.98 Bi 0.02 S 4.4 7 O 0.03 Cl 1.5The raw material is 2.02 mol of Li 2 S, 1.5 mol LiCl, 0.49 mol P 2 S 5 and 0.01 mol Bi 2 O 3 .

[0099] Embodiment 23

[0100] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 The raw material is 2.1 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.05 mol Bi 2 O 3 .

[0101] Embodiment 24

[0102] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.54 P 0.98 Bi 0.02 S 4.4 7 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw material is 2.02 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P 2 S 5 and 0.01 mol Bi 2 O 3 .

[0103] Embodiment 25

[0104] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.52 P 0.99 In 0.01 S 4.48 5 O 0.015 Cl 1.5 The raw material is 2.01 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2S 5 and 0.005 mol In 2 O 3 .

[0105] Embodiment 26

[0106] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.54 P 0.98 In 0.02 S 4.4 7 O 0.03 Cl 1.5 The raw material is 2.02 mol of Li 2 S, 1.5 mol LiCl, 0.49 mol P 2 S 5 and 0.01 mol In 2 O 3 .

[0107] Embodiment 27

[0108] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 The raw material is 2.1 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.05 mol In 2 O 3 .

[0109] Embodiment 28

[0110] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.54 P 0.98 In 0.02 S 4.4 7 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw material is 2.02 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P 2 S 5 and 0.01 mol In 2 O 3 .

[0111] Embodiment 29

[0112] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.53 P 0.99 Mg 0.01 S 4.4 9 O 0.01 Cl 1.5 The raw material is 2.015 mol of Li 2 S, 1.5 mol LiCl, 0.495 mol P 2 S 5 and 0.01 mol of MgO.

[0113] Embodiment 30

[0114] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.56 P 0.98 Mg 0.02 S 4.4 8 O 0.02 Cl 1.5 The raw material is 2.03 mol of Li 2 S, 1.5 mol LiCl, 0.49 mol P 2 S 5 and 0.02 mol of MgO.

[0115] Embodiment 31

[0116] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 The raw material is 2.15 mol of Li 2 S, 1.5 mol LiCl, 0.45 mol P 2 S 5 and 0.1 mol of MgO.

[0117] Embodiment 32

[0118] The difference between this embodiment and embodiment 3 is that the chemical formula of the second electrolyte is Li 5.56 P 0.98 Mg 0.02 S 4.4 8 O 0.02 Cl 1.3 Br0.1 I 0.1 The raw material is 2.03 mol of Li 2 S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P 2 S 5 and 0.02 mol of MgO.

[0119] Embodiment 33

[0120] The difference between this embodiment and embodiment 3 is that during the preparation of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer, ETFE is selected as the first binder.

[0121] Embodiment 34

[0122] The difference between this embodiment and embodiment 3 is that during the preparation of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer, PCTFE is selected as the first binder.

[0123] Embodiment 35

[0124] The difference between this embodiment and embodiment 3 is that the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer are prepared by a wet coating method.

[0125] Specifically, in this embodiment, the first solid electrolyte layer is prepared by: 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5 The electrolyte material, SBR binder and xylene solvent were mixed in a mass ratio of 49:1:50 to form an electrolyte slurry, and the electrolyte slurry was scraped onto a smooth aluminum foil using a 5 μm film applicator and vacuum dried at 80 °C to form a 5 μm thick Li 2.35 Zr 0.65 Fe 0.35 Cl 5 Br 0.5 I 0.5 A first solid electrolyte layer.

[0126] Preparation of the second solid electrolyte layer: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5The electrolyte material, SBR binder and xylene solvent were mixed uniformly in a mass ratio of 49:1:50 to prepare an electrolyte slurry, and the electrolyte slurry was scraped onto a smooth aluminum foil using a 20 μm film applicator and vacuum dried at 80 °C to prepare a 20 μm thick Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 A second solid electrolyte layer.

[0127] Preparation of the third solid electrolyte layer: 80wt% Li 10 G 2 S 12 Electrolyte materials and 20 wt% Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The electrolyte materials were mixed evenly to obtain a mixed electrolyte material. Then, the mixed electrolyte material, SBR binder and xylene solvent were mixed evenly in a mass ratio of 49:1:50 to prepare an electrolyte slurry, and the electrolyte slurry was scraped onto a smooth aluminum foil using a 5 μm film applicator, and vacuum dried at 80°C to prepare a 5 μm thick third solid electrolyte layer.

[0128] Embodiment 36

[0129] The difference between this embodiment and Embodiment 35 is that during the preparation of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer, PVDF is selected as the second binder.

[0130] Embodiment 37

[0131] The difference between this embodiment and Embodiment 35 is that during the preparation of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer, PAA is selected as the second binder.

[0132] Comparative Example 1

[0133] The difference between this comparative example and Example 3 is that the chemical formula of the second electrolyte is Li 5.5 PS 4.5 Cl 1.5 The raw material is 2 mol of Li 2 S, 1.5 mol LiCl and 0.5 mol P 2 S 5 .

[0134] Comparative Example 2

[0135] The difference between this comparative example and Example 3 is that the solid electrolyte membrane only includes the first solid electrolyte layer.

[0136] Comparative Example 3

[0137] The difference between this comparative example and Example 3 is that the solid electrolyte membrane only includes the second solid electrolyte layer.

[0138] Comparative Example 4

[0139] The difference between this comparative example and Example 3 is that the solid electrolyte membrane only includes the third solid electrolyte layer.

[0140] The compositions and parameters of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer in each embodiment and comparative example are shown in Table 1.

[0141] Table 1. Composition of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer in Examples 1 to 37 and Comparative Examples 1 to 4

[0142]

[0143]

[0144]

[0145] In the present invention, performance tests were performed on all-solid-state batteries prepared using different solid electrolyte membranes in Examples 1 to 37 and Comparative Examples 1 to 4.

[0146] See also Figure 3 As shown, in one embodiment of the present invention, the morphology of the solid electrolyte membrane in Example 3 is characterized by, for example, a scanning electron microscope. The magnification of the scanning electron microscope is, for example, 10,000 times. Figure 3 It can be seen that the first solid electrolyte layer and the second solid electrolyte layer prepared by the powder extrusion molding method have good self-supporting properties and can stably exist between the positive electrode and the negative electrode, thereby facilitating better performance of the solid electrolyte membrane.

[0147] See also Figure 4 As shown, in one embodiment of the present invention, for example, the all-solid-state battery in Example 3 is subjected to a room temperature cycle performance test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V to obtain the capacity (CC) and coulombic efficiency (CE) at different cycle numbers. Figure 4It can be seen that with the increase in the number of cycles, the attenuation trend of the battery capacity is relatively gentle, and the coulombic efficiency of the battery does not fluctuate and stabilizes at around 100%, which indicates that the battery has good cycle performance.

[0148] Please refer to Table 2. In one embodiment of the present invention, for example, the all-solid-state batteries in Examples 1 to 37 and Comparative Examples 1 to 4 are subjected to a room temperature cycle stability test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V. The test is terminated when the battery capacity reaches 80% of the first cycle capacity State of Health (SOH), and the number of room temperature cycles of the battery is recorded. The recorded results are shown in Table 2.

[0149] Table 2. Test results of all-solid-state batteries in Examples 1 to 37 and Comparative Examples 1 to 4

[0150]

[0151]

[0152] Please refer to Table 1 and Table 2. Comparative Example 3 and Comparative Examples 2 to 4 show that if the first solid electrolyte layer is used alone as the solid electrolyte membrane, the number of normal temperature cycles of the battery is 13, and a short circuit occurs. If the second solid electrolyte layer is used alone as the solid electrolyte membrane, the number of normal temperature cycles of the battery is 451. If the third solid electrolyte layer is used alone as the solid electrolyte membrane, the number of normal temperature cycles of the battery is only 12, and there is almost no cycle performance. However, if the first solid electrolyte layer, the third solid electrolyte layer and the second solid electrolyte layer are sequentially compounded as the solid electrolyte membrane, the number of normal temperature cycles of the battery increases to 1646, which shows that: in the solid electrolyte membrane, the first solid electrolyte layer can widen the electrochemical window of the solid electrolyte membrane, so that the solid electrolyte membrane can adapt to the high-voltage positive electrode and the lithium metal negative electrode, the second solid electrolyte layer can improve the electrochemical reduction stability of the solid electrolyte membrane, and the third solid electrolyte layer can consume the generated lithium dendrites, prevent the lithium dendrites from penetrating, avoid short circuits in the all-solid-state battery, and ensure that the all-solid-state battery can still operate stably and safely at high rates, thereby improving the cycle performance of the battery.

[0153] Please refer to Table 1 and Table 2. By comparing Examples 1 to 4, it can be seen that as the third electrolyte Li 10 G 2 S 12As the proportion of the third electrolyte increases, the ionic conductivity of the third solid electrolyte layer gradually increases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the content of the third electrolyte in the third solid electrolyte layer, the cycle performance of the battery can be improved.

[0154] Please refer to Table 1 and Table 2. By comparing Examples 3, 5 and 6, it can be seen that in the three third electrolytes Li 10 G 2 S 12 , Li 10 Ge 0.5 Sn 0.5 P 2 S 12 and Li 10 Ge 0.5 Si 0.5 P 2 S 12 In, Li 10 G 2 S 12 The number of cycles at room temperature of the battery assembled as the third electrolyte is the largest, indicating that: 10 Ge 1-i G i P 2 S 12 In the embodiment, when i is 0, the cycle performance of the battery is the best. Therefore, by controlling the doping amount of Ge and G elements in the third electrolyte, the cycle performance of the battery can be improved.

[0155] Please refer to Table 1 and Table 2. By comparing Example 3 with Examples 7 to 9, it can be seen that as the thickness of the first solid electrolyte layer increases from 1 μm to 100 μm, the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. By comparing Example 3 with Examples 10 to 12, it can be seen that as the thickness of the third solid electrolyte layer increases from 1 μm to 100 μm, the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. By comparing Example 3 with Examples 13 to 15, it can be seen that as the thickness of the second solid electrolyte layer increases from 1 μm to 150 μm, the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the thickness of the first solid electrolyte layer, the second solid electrolyte layer, and the third solid electrolyte layer, the cycle performance of the battery can be improved.

[0156] Please refer to Table 1 and Table 2. By comparing Example 3, Example 16 and Example 17, it can be seen that as the doping amount of the Fe element in the first solid electrolyte layer increases, the ionic conductivity of the first solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, in the first solid electrolyte layer, by controlling the doping amount of the M element in the first electrolyte, the cycle performance of the battery can be improved.

[0157] Please refer to Table 1 and Table 2. By comparing Example 3, Example 18 and Example 19, it can be seen that with the increase in the doping amount of the Sb element in the second electrolyte, the ionic conductivity of the second solid electrolyte layer and the third solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. By comparing Examples 21 to 23, it can be seen that with the increase in the doping amount of the Bi element in the second electrolyte, the ionic conductivity of the second solid electrolyte layer and the third solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. By comparing Examples 25 to 27, it can be seen that with the increase in the doping amount of the In element in the second electrolyte, the ionic conductivity of the second solid electrolyte layer and the third solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the T element in the second electrolyte, the cycle performance of the battery can be improved.

[0158] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 29 to 31 that as the doping amount of the Mg element in the second electrolyte increases, the ionic conductivity of the second solid electrolyte layer and the third solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the E element in the second electrolyte, the cycle performance of the battery can be improved.

[0159] Refer to Table 1 and Table 2. By comparing Examples 3 and 20, Examples 22 and 24, Examples 26 and 28, and Examples 30 and 32, it can be seen that when the doping amount of Sb, In, Bi or Mg in the second electrolyte is the same, if Br and I are also doped into the second electrolyte, the ionic conductivity of the second solid electrolyte layer and the third solid electrolyte layer will decrease, and the number of normal temperature cycles of the battery will decrease, that is, the cycle performance of the battery will be reduced. Therefore, by controlling the number of element types contained in X or Q in the second electrolyte, the cycle performance of the battery can be improved.

[0160] Please refer to Table 1 and Table 2. By comparing Example 3, Example 22, Example 26, Example 30 and Comparative Example 1, it can be seen that when the second electrolyte is not doped with Sb, Bi, In or Mg elements, the ionic conductivity of the second solid electrolyte layer and the third solid electrolyte layer will increase, but the number of cycles of the battery at room temperature is only 85, and there is almost no cycle performance, which shows that the Sb, Bi, In or Mg elements doped in the second electrolyte can significantly improve the cycle performance of the battery. Therefore, by controlling the type of elements T or E in the second electrolyte, the cycle performance of the battery can be improved.

[0161] Please refer to Table 1 and Table 2. By comparing Example 3, Example 33 and Example 34, it can be seen that the first binder used in the preparation process of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer is different, resulting in different ionic conductivities of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer, and also resulting in different cycle performances of the battery. Specifically, when PTFE is used as the first binder, the ionic conductivity of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer is the largest, and the number of normal temperature cycles of the battery is also the largest, that is, the cycle performance of the battery is the best.

[0162] Please refer to Table 1 and Table 2. By comparing Example 3 and Examples 35 to 37, it can be seen that the preparation methods of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer are different, resulting in different ionic conductivities of the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer, and also resulting in different cycle performances of the battery. Specifically, compared with the wet coating method, the first solid electrolyte layer, the second solid electrolyte layer and the third solid electrolyte layer prepared by the powder extrusion molding method have the largest ionic conductivity, and the number of normal temperature cycles of the assembled battery is also the largest, that is, the cycle performance is the best.

[0163] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.

[0164] In summary, the present invention proposes an all-solid-state battery and its application. By sequentially compounding a first solid electrolyte layer, a third solid electrolyte layer and a second solid electrolyte layer, a multifunctional asymmetric self-supporting solid electrolyte membrane is prepared, which can improve the compatibility between the solid electrolyte membrane and the positive and negative electrodes, widen the electrochemical window of the solid electrolyte membrane, and thus improve the stability of the all-solid-state battery. It can improve the resistance of the solid electrolyte membrane to lithium dendrite penetration, avoid short circuits in the battery, and ensure that the all-solid-state battery can still operate stably and safely at high rates, thereby improving the safety and cycle life of the battery. It can improve the ionic conductivity of the solid electrolyte membrane, thereby improving the working efficiency of the battery. It can improve the electrochemical reduction stability of the solid electrolyte membrane, so that the solid electrolyte membrane can effectively resist problems such as reduction reactions and electrode interface instability.

[0165] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0166] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. An all-solid-state battery, characterized in that: At least: The first solid electrolyte layer is arranged on the positive electrode side of the all-solid-state battery, and the ion conductivity of the first solid electrolyte layer is 1×10 -4 S / cm~1×10 -2 S / cm; The second solid electrolyte layer is arranged on the negative electrode side of the all-solid-state battery, and the ion conductivity of the second solid electrolyte layer is 1×10 -3 S / cm~2×10 -2 S / cm; as well as The third solid electrolyte layer is disposed between the first solid electrolyte layer and the second solid electrolyte layer, and the ionic conductivity of the third solid electrolyte layer is 1×10 -3 S / cm~2×10 -2 S / cm.

2. The all-solid-state battery according to claim 1, characterized in that: The first solid electrolyte layer includes a first electrolyte, the chemical formula of which is Li 2+n Zr 1-n M n Cl 6-x-y Br x I y , wherein 0≤n≤0.6, 0≤x≤6, 0≤y≤6, x+y≤6, and M is selected from at least one of V, Cr, Mn, Fe, Co and Ni.

3. The all-solid-state battery according to claim 2, characterized in that: M is Fe, and the value range of n is 0.01≤n≤0.

5.

4. The all-solid-state battery according to claim 1, characterized in that: The second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is Li a P 1-b T b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, T is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb, and X is selected from at least one of Cl, Br or I.

5. The all-solid-state battery according to claim 4, characterized in that: T is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 <b≤0.1。 6. The all-solid-state battery according to claim 1, characterized in that: The second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, or Pb, and Q is selected from at least one of Cl, Br, or I.

7. The all-solid-state battery according to claim 6, characterized in that: E is Mg, Q is Cl, and the value range of g is 0.01≤g≤0.

1.

8. The all-solid-state battery according to any one of claims 4 to 7, characterized in that: The third solid electrolyte layer includes the second electrolyte and a third electrolyte, and the chemical formula of the third electrolyte is Li 10 Ge 1-i G i P2S 12 , wherein 0≤i<1, and G is selected from at least one of Si or Sn.

9. The all-solid-state battery according to claim 8, characterized in that: In the third solid electrolyte layer, the content of the second electrolyte is 1 wt%-95 wt%, and the content of the third electrolyte is 5 wt%-99 wt%.

10. The all-solid-state battery according to claim 1, characterized in that: The thickness of the first solid electrolyte layer is 1 μm-100 μm, the thickness of the second solid electrolyte layer is 1 μm-150 μm, and the thickness of the third solid electrolyte layer is 1 μm-100 μm.

11. An electronic device, characterized in that: An all-solid-state battery comprising any one of claims 1-10.

Citation Information

Cited By

  • Three-layer heterogeneous integrated solid electrolyte membrane, preparation method thereof and all-solid-state lithium battery

    CN121331919A